ANALISIS KESESUAIAN LAHAN MANGROVE UNTUK PENGEMBANGAN EKOWISATA PANTAI HUTA HUTAN MANGROVE KABUPATEN SERDANG BEDAGAI PROVINSI SUMATERA UTARA - Putri Winda Sidabutar; Welmar Olfan Basten Barat; Ria Retno (Journal of Research and Publication Innovation, 2025)
Serdang Bedagai Regency is an administrative area located on the coast and has Huta Beach Mangrove Forest. Some mangrove areas are located in Huta Mangrove Forest Beach. The land condition of mangrove areas as part of ecotourism development is the subject of this study. The data collection method is based on primary and secondary data, and then analyzed with quantitative and qualitative data. The results showed that Mangrove Forest Beach mangrove ecotourism in the Conditionally Suitable (S3) category has a tourism suitability index (IKW) of 37%, 27%, 37%, 32%, 37%, 37%, and 42% at stations 1,2,3,4,5,6, and 7. The types of mangroves found at each observation station are Avicennia officinalis and Rhizopora mucronata.